2021
DOI: 10.5194/acp-21-13397-2021
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire smoke, Arctic haze, and aerosol effects on mixed-phase and cirrus clouds over the North Pole region during MOSAiC: an introduction

Abstract: Abstract. An advanced multiwavelength polarization Raman lidar was operated aboard the icebreaker Polarstern during the MOSAiC (Multidisciplinary drifting Observatory for the Study of Arctic Climate) expedition to continuously monitor aerosol and cloud layers in the central Arctic up to 30 km height. The expedition lasted from September 2019 to October 2020 and measurements were mostly taken between 85 and 88.5∘ N. The lidar was integrated into a complex remote-sensing infrastructure aboard the Polarstern. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 127 publications
(196 reference statements)
4
66
1
Order By: Relevance
“…During the 1-year MOSAiC expedition the multiwavelength polarization Raman lidar Polly (POrtabLe Lidar sYstem; Engelmann et al, 2016) was continuously operated on board the Polarstern. An overview of the Polarstern lidar instrument and all retrievable aerosol products is given by Engelmann et al (2021). Continuous, automated measurements of aerosol and cloud profiles up to stratospheric heights were collected from 26 September 2019 to 2 October 2020.…”
Section: Mosaic Lidar Data Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…During the 1-year MOSAiC expedition the multiwavelength polarization Raman lidar Polly (POrtabLe Lidar sYstem; Engelmann et al, 2016) was continuously operated on board the Polarstern. An overview of the Polarstern lidar instrument and all retrievable aerosol products is given by Engelmann et al (2021). Continuous, automated measurements of aerosol and cloud profiles up to stratospheric heights were collected from 26 September 2019 to 2 October 2020.…”
Section: Mosaic Lidar Data Analysismentioning
confidence: 99%
“…vanced multiwavelength polarization Raman lidar was operated on board the German icebreaker Polarstern (Knust, 2017), which served as the main MOSAiC platform for advanced remote sensing studies of the atmosphere. The ice breaker was trapped in the ice from October 2019 to May 2020 and drifted through the Arctic Ocean at latitudes mainly between 85 and 88.5 • N for 7.5 months, continuously monitoring aerosol and cloud layers in the central Arctic up to 30 km height (Engelmann et al, 2021). MOSAiC was the largest Arctic field campaign ever conducted.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Later on, Baars et al (2019) reported 6 months of observations (from August 2017 to January 2018) of such wildfire smoke aerosols during the episode with a network of 28 EARLINET ground-based lidars in Europe, showing the aerosol properties and the evolution of the smoke layer during the long-range transport. Recently, wildfire smoke layers were measured over the North Pole with a lidar aboard the icebreaker Polarstern during the MOSAiC (Multidisciplinary drifting Observatory for the Study of Arctic Climate) expedition (Engelmann et al, 2021;Ohneiser et al, 2021). However, the spatial resolution remains sparse, as advanced lidars are expensive.…”
mentioning
confidence: 99%